Correlation between Family Support with Sexual Behavior and Antiretroviral Adherence on HIV/AIDS Patients in “A” Community Bandung - Siska Febriyanti; July Ivone; Limdawati Kwee (Universitas Kristen Maranatha, 2023)
Family support is the attitude, action, and acceptance of the family towards its members. One of the functions of the family is to support the health care of other family members. HIV (Human Immunodeficiency Virus) is a retrovirus that attacks the immune system of CD4+ cells, and if not treated immediately, the patient will fall into an AIDS (Acquired Immunodeficiency Syndrome) condition. HIV/AIDS patients need support from both social and family. The incidence of HIV/AIDS in West Java during 2019 was ranked third in Indonesia, which was 6,066 patients. The aim of this study was to determine the relationship between family support with patient’s sexual behavior and adherence to taking antiretroviral drugs. The research method used is an analytical method with a cross-sectional design. The sample of this study was HIV patients who are members of Community